PENGUNGKAPAN TANGGUNG JAWAB SOSIAL LEMBAGA PERKREDITAN DESA (LPD) BERDASARKAN FILOSOFI TRI HITA KARANA - EKA DAMAYANTHI, I G.A. (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
The philosophy of Tri Hita Karana has been implemented in the social system of Hindu and nonHindu Balinese society. This philosophy emphasize on harmonizing relationship of human to the God (Parhyangan), human to human (Pawongan), and human to the environment (Palemahan). LPD as the custom village financial institution has a social responsibility to the society. This article explains that as a financial institution raising capital from the society has social and economic responsibility to them. According to Regional Act of Bali Province No.8 Year 2002, twenty percent of LPD’s net income shall be provided for the village development plan, and 5 percent for social fund of the village. This shows the role of LPD in increasing the society welfare. This article also describes several implementations of social responsibilities of LPD with Tri Hita Karana philosophy. To be able to show the responsibility, it is suggested for LPD to prepare social responsibility report periodically.
Keywords: financial instutition, LPD, social responsibility, Tri Hita Karana